Metagenomic evidence for co-occurrence of antibiotic, biocide and metal resistance genes in pigs. (January 2022) - Li, Xuanji; Rensing, Christopher; Vestergaard, Gisle; Arumugam, Manimozhiyan; Nesme, Joseph; Gupta, Shashank; Brejnrod, Asker Daniel; Sørensen, Søren Johannes
Highlights: A comprehensive gut microbiome metagenomic analysis of 278 pigs was conducted. Co-selection phenomena were investigated via co-occurrence patterns as a proxy. Twenty-seven types of co-occurrences involving 131 resistance genes were detected. Regardless of use of antibiotics, AMR can be maintained by co-occurrence with MRGs/BRGs. Maintenance of AMR is not a random selection process but pertains to specific phylogenetic clades. Abstract: Antibiotic-resistant pathogens constitute an escalating public health concern. Hence a better understanding of the underlying processes responsible for this expansion is urgently needed. Co-selection of heavy metal/biocide and antibiotic resistance genes (ARGs) has been suggested as one potential mechanism promoting the proliferation of antimicrobial resistance (AMR). This paper aims to elucidate this interplay and exploit differences in antibiotic usage to infer patterns of co-selection by the non-antibiotic factors metals and biocides in the context of pig farming. We examined 278 gut metagenomes from pigs with continuous antibiotic exposure, only at weaning and at no exposure. Metals as growth promoters and biocides as disinfectants are currently used with little restrictions in stock farming. The pigs under continuous antibiotic exposure displayed the highest co-occurrence of ARGs and other genetic elements while the pigs under limited use of antibiotics still showed abundant co-occurrences. Pathogens belonging to Enterobacteriaceae displayed increased co-occurrence phenomena, suggesting that this maintenance is not a random selection process from a mobilized pool but pertains to specific phylogenetic clades. These results suggest that metals and biocides displayed strong selective pressures on ARGs exerted by intensive farming, regardless of the current use of antibiotics.